Sistem First To File Sebagai Perlindungan Hukum Dalam Hukum Merek: Studi Putusan Mahkamah Agung Nomor 57/Pdt.Sus- Merek/2019/Pn Niaga Jkt.Pst - Dezza Al Manda; Raditya Permana; Faris Satria Alam (JOURNAL of LEGAL RESEARCH, 2022)
In this study, we will look into the First to File system and the principle of equality in the law on trademarks and geographical indications. We will also look into how the judges looked at the Geprek Bensu case in the Supreme Court Decision Number 57/2018/PN Niaga Jkt.Pst. First to File is the most important thing in Law Number 20 of 2016, which deals with trademarks and geographical indications. It is the first step to a chance. Article 3 of Law Number 20 of 2016 says that if the mark has been registered in the General Register of Marks, you can get the right to a mark. Even though the law doesn't say it, this is what it says (DUM). It was found that Ruben Samuel Onsu was not careful when he tried to use the Geprek Bensu trademark. The Supreme Court ruled that he broke the First to File system. The results of this study show that some Indonesian people haven't paid much attention to the First to File system. One of them is Ruben Samuel Onsu. It was finally up to the judge in this case to decide that he didn't believe the Plaintiff, Ruben Samuel Onsu, and that he wanted the Director General of Trademarks and Geographical Indicators to remove the registration of the marks in the name of Ruben Samuel Onsu.